2000
DOI: 10.1097/00000478-200005000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Follicular Lymphoma in the Duodenum

Abstract: The incidence of indolent lymphomas in the lymph nodes and extranodal regions is quite different. Follicular lymphoma (FL) is most common in the nodes, and it seems to be least common in the gastrointestinal (GI) tract, where mucosa-associated lymphoid tissue lymphoma arises most frequently. The authors report that the incidence of FL is unexpectedly high in the duodenum compared with other portions of the GI tract. FL was detected in only eight of 222 cases of GI lymphoma (3.6%). However, five cases of FL aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
175
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 17 publications
12
175
0
Order By: Relevance
“…predominance of duodenal involvement of FL is in agreement with most previous studies, 3,6,7,9,14 However, LeBrun et al 21 and Damaj et al 15 reported that the ileum was the most frequent site. In recent studies that evaluated an extensive area of the small intestine by DBE, involvement of the jejunum and/or the ileum was identified in 80% to 100% of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…predominance of duodenal involvement of FL is in agreement with most previous studies, 3,6,7,9,14 However, LeBrun et al 21 and Damaj et al 15 reported that the ileum was the most frequent site. In recent studies that evaluated an extensive area of the small intestine by DBE, involvement of the jejunum and/or the ileum was identified in 80% to 100% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…[2][3][4] Recently, balloon-assisted enteroscopies-that is, double-balloon endoscopy (DBE) and single-balloon endoscopy (SBE)-have enabled the examination of an extensive area of the small bowel and the detection of diminutive small intestinal lesions. The usefulness of DBE for the practical diagnosis of intestinal FL has been reported in several publications.…”
mentioning
confidence: 99%
“…These rare FLs harbor the t(14;18) involving IgH/BCL-2 as determined by polymerase chain reaction, evolve in the gut mucosa, express the mucosal homing integrin a4b7, typically express IgA and have a low tendency to spread systemically and by consequence have a good clinical prognosis. [4][5][6]83 These features indicate that GI-FLs originate from local, antigen-responsive precursor cells and their sessile nature suggests continued dependence on Ags, for example, originating from the gut lumen, also during the tumor stage. 4 It has been reported that in 55 of 79 FLs analyzed (79%), replacement mutations in IgV H result in generation of aminoacid motifs being potential N-glycosylation sites.…”
Section: The Role Of the B-cell Antigen Receptor Complex In Fl Develomentioning
confidence: 99%
“…1 Although they express CD10 and bcl-2 and harbor t(14;18) translocation similar to nodal follicular lymphomas, 2 most of them are obviously at lower clinical stages than the nodal cases (most are stage I-II) and have lower histological grading with rather dominantly uniform intermediate small cleaved cells.…”
mentioning
confidence: 99%